Abnormalities of language pathways in schizophrenia patients with and without a lifetime history of auditory verbal hallucinations: A DTI-based tractography study. (3rd October 2017) - Leroux, Elise; Delcroix, Nicolas; Dollfus, Sonia
Abstract: Objectives: Auditory verbal hallucinations (AVHs) are frequently observed in patients with schizophrenia (SZ) and could be the result of white matter (WM) fibre abnormalities involved in speech production/comprehension and perception. We evaluated WM integrity changes in SZ with (SZ+) and without (SZ–) lifetime AVHs compared to healthy controls (HCs), using diffusion tensor imaging-based tractography, with a novel focus on the structural connectivity within both intra- and interhemispheric fasciculi. Methods: The study included 27 SZ+, 12 SZ– and 34 HCs. Fractional anisotropy (FA) and mean and radial diffusivities (MD and RD) were extracted in each participant in two left interhemispheric fasciculi and in the interhemispheric auditory pathway (IAP) to test integrity differences among groups. Results: SZ– and SZ + compared to HCs presented increased diffusivities and/or decreased FA in the interhemispheric fasciculi. Decreased FA was significant only between SZ + and HCs for the IAP. Conclusions: In this first comparison of integrity changes within both intra- and interhemispheric fasciculi, abnormalities in the intrahemispheric fasciculi were observed in both SZ– and SZ+, but an alteration in the IAP was seen only in SZ+. These results suggest that the IAP may be more involved in patients with AVHs-proneness.